Pengaruh Pengetahuan Peraturan Pajak, Pemanfaatan Kebijakan PPS dan Kesadaran Pajak Owner E-Commerse terhadap Kepatuhan Pajak - Rista Ninda Silfiana; Lintang Venusita (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to find out about the behavior of individual taxpayers in fulfilling tax responsibilities that have been carried out, the use of applicable PPS policies and the tax knowledge of these individual taxpayers in paying their taxes. Quantitative method is the method chosen for this research. The data collection was obtained from the answers to the questionnaire. Individual taxpayers who own e-commerce businesses in Lamongan Regency are the population of this study. The number of samples obtained is 80 samples. Purposive sampling technique was applied for sampling and data processing using SmartPLS 3.0. The results obtained from knowledge of tax regulations and the use of PPS policies do not have an effect on tax compliance, it is different from the awareness of taxpayers that influences tax compliance. This study has several limitations, including: using only 3 variables (knowledge of tax regulations, utilization of PPS policies, and tax awareness), conducted in one location (Lamongan), with only 80 samples. Further research is suggested to expand the research area and increase the number of samples in order to produce better data. Additional variables related to WPOP compliance can also be added.